Are returns on Foreign Direct Investment (FDI), FDI determinants? - Lannutti, Luigi (2016)
Foreign Direct Investments (FDI) acquired an important role in the development process of the global economy. FDI inward stock was equivalent to an average of 32% of GDP for OECD countries in 2013. However, FDI affects a country’s Balance of Payments (BoP) in two ways: FDI flows are recorded in the BoP financial account while returns on FDI affect the BoP current account. Therefore, part of the positive contribution of inward FDI to a country on its financial account could be potentially offset by a negative contribution of FDI returns on the current account. The intent of this work is to complement the research on FDI determinants by introducing FDI returns as a variable in a gravity model where bilateral FDI outflows are the dependent variable. Moreover, using outward FDI flows as the dependent variable, the work allows looking at the behavior of Multinational Corporations (MNC) investing abroad. The results show that MNCs repatriate returns generating from the investments they make abroad. This is particularly true when high-income countries are involved: MNCs from high-income countries repatriate returns to their home countries from FDI made anywhere, while MNCs from middle-income countries repatriate returns from FDI in high-income countries. Repatriated returns are a relevant variable determining the value of FDI that a country makes in another country. The information on FDI returns is starting to become available to the public. This allows MNCs to sharpen their investment location decision models and national IPAs to better assess the two-fold BoP effects of promoting FDI.